Pergeseran Pola Komunikasi Keluarga di Kalangan Remaja akibat Telepon Pintar - Jonathan, Vincentius Allerio; Loisa, Riris (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
The development of digital technology, particularly smartphones, has brought significant changes to family communication patterns, especially among adolescents. Smartphones have become the primary tools for communication and entertainment, but their use often replaces deeper face-to-face interactions. Based on the theory of technological determinism, smartphones not only influence how humans interact but also shape communication patterns and social relationships. Teenagers begin to learn how to deal with complex emotions, including uncertainty, confusion, and the need to discover their identity. In addition, adolescents are in a phase where self-control and emotional regulation are greatly tested. This study aims to understand the communication patterns of adolescent smartphone users within families in the digital era. The findings indicate that family interactions tend to become more functional, with communication more frequently occurring through digital devices. Excessive smartphone use also has the potential to reduce the quality of emotional communication within families, although it allows adolescents to remain virtually connected. Technology management strategies to maintain the quality of interpersonal relationships in the digital era. Perkembangan teknologi digital, khususnya telepon pintar, telah membawa perubahan besar dalam pola komunikasi keluarga, terutama di kalangan remaja. Telepon pintar menjadi alat utama untuk komunikasi dan hiburan, tetapi penggunaannya sering kali menggantikan interaksi tatap muka yang lebih mendalam. Berdasarkan teori determinisme teknologi, telepon pintar tidak hanya memengaruhi cara manusia berinteraksi, tetapi juga membentuk pola komunikasi dan hubungan sosial. Remaja mulai belajar bagaimana menghadapi emosi kompleks, termasuk ketidakpastian, kebingungan, serta kebutuhan untuk menemukan jati diri. Selain itu, remaja berada dalam fase di mana kontrol diri dan regulasi emosi sangat diuji. Penelitian ini bertujuan untuk memahami pola komunikasi remaja pengguna telepon pintar dalam keluarga di era digital. Hasil penelitian menunjukkan bahwa interaksi keluarga cenderung berubah menjadi lebih fungsional, dengan komunikasi yang lebih sering terjadi melalui perangkat digital. Penggunaan telepon pintar secara berlebihan juga berpotensi mengurangi kualitas komunikasi emosional dalam keluarga, meskipun memungkinkan remaja tetap terhubung secara virtual. Strategi pengelolaan penggunaan teknologi untuk menjaga kualitas hubungan interpersonal di tengah era digital.